Flexural behavior of large scale semi-precast reinforced concrete T-beams made of natural and recycled aggregate concrete. (1st November 2019) - Fahmy, Mohamed F.M.; Idriss, Lamiaa K.
Highlights: New hybrid structural system using recycled aggregate concrete in modern prefabricated structures. Innovative accelerated construction technology for RC buildings. Damage-controlled behavior using recycled concrete blocks as filler for semi-precast beam. Integrated flexural behavior of the natural and recycled aggregate concrete in one section. Abstract: This study aimed to investigate the flexural behavior of T-section semi-precast reinforced concrete (RC) beams composed of recycled aggregate concrete (RAC) and natural aggregate concrete (NAC). The experimental program consisted of four large-scale T beams, including three semi-precast T-beams and a reference RC T-beam made of traditionally cast high strength natural aggregate concrete (HSNAC). The web of all the semi-precast beams composed of a precast U-shaped part, which contained the longitudinal and transverse reinforcement and was cast of HSNAC, and an inner RAC core. Normal strength RAC (NSRAC) or high strength RAC (HSRAC) was used as web core filler, and HSNAC or HSRAC was used for the beam flange. Two techniques were adopted to fill the web core: the traditional concrete casting and the placement of well-sized precast concrete blocks. The results indicated the applicability of RAC and NAC in one section to achieve comparable strength, deformability, and failure mode to those of the monolithically cast beam with NAC. In addition, using precast RAC blocks as filler in the web core of RC beams is a promising construction technique, which can be adopted as a critical design parameter to control development, propagation, and width of flexural and shear cracks to a large extent.